2016
DOI: 10.15376/biores.11.4.8638-8652
|View full text |Cite
|
Sign up to set email alerts
|

Impact Bending Strength and Brinell Hardness of Densified Hardwoods

Abstract: The objective of this research was to determine the influence of wood species (Fagus sylvatica L. and Populus tremula L.), thickness (4, 6, 10, 18 mm), and degree of densification (0%, 10%, and 20%) on the impact bending strength (IBS) and Brinell hardness (BH) in the radial direction. Three-factor analysis of variance confirmed that the difference in IBS was significantly related to the wood species and wood thickness. Wood densification did not have a significant effect on IBS. In addition, beech wood exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…This was due to the fact that when the intender was pressed into the sample, the wood surrounding the intender was deformed and entirely densified. Consequently, this additionally affects the density and hardness of the near-surface layer (Gašparík et al 2016). As a result, the interdependence between DMaxL, ADMaxL, and the hardness of surface-densified wood was in some measure disturbed.…”
Section: Fig 5 Brinell Hardness Of Surface-densified Birch Woodmentioning
confidence: 99%
See 1 more Smart Citation
“…This was due to the fact that when the intender was pressed into the sample, the wood surrounding the intender was deformed and entirely densified. Consequently, this additionally affects the density and hardness of the near-surface layer (Gašparík et al 2016). As a result, the interdependence between DMaxL, ADMaxL, and the hardness of surface-densified wood was in some measure disturbed.…”
Section: Fig 5 Brinell Hardness Of Surface-densified Birch Woodmentioning
confidence: 99%
“…The course of the densification process is determined by the type of wood, density, moisture of wood, the method of cutting specimens, i.e. the arrangement of annual growth rings in the wood cross-section, the thickness of the specimens, the pressing pressure, and the temperature and time of pressing (Ülker et al 2012;Budakçı et al 2016;Gašparík et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The mean difference in the hardness values was approximately 110%, while the density values were higher in samples with a compression ratio of 50% (768 kg/m 3 ) than in the undensified samples (395 kg/m 3 ). In other studies, it has been reported that the hardness of woody materials is closely related to the compression ratio, and that the hardness values increase as the compression ratio is increased (Ünsal et al 2011;Gašparík et al 2016). The correlation between the radial hardness and the air-dried density of the samples that underwent thermal treatment and the control are shown in Fig.…”
Section: Radial Hardness Analysismentioning
confidence: 72%
“…These results were due to the degradation of the structure when more aggressive thermal treatment is applied. Thermal treatments caused the increase of micro-fractures, (Ulker et al 2012, Navi and Pizzi 2015, Gašparík et al 2016, Gaff et al 2017, Pertuzzatti et al 2018) and the hot oil at 180 °C further weakened the structure because the it penetrated the surface and facilitated the heat transfer with consequent increase of degradation inside of the wood structure.…”
Section: Mechanical Propertiesmentioning
confidence: 99%